A case report: delayed right ventricular pericardial fistula and aneurysm following penetrating traumatic injury—a controversial aetiology. Issue 4 (17th July 2020) - Steinmaurer, Martina; Cupido, Blanche; Hannington, Matthew; Manganyi, Rodgers
Abstract: Background: Right ventricular aneurysms (RVAs) are rare. We present a case with a combined RVA and right ventricular pericardial fistula resulting in a pericardial effusion and cardiac tamponade. The RVA was detected 47 days after the patient suffered a gunshot wound. This report adds to the body of scarce literature on RVA aetiology, diagnoses, and treatment. Case summary: A 30-year-old male patient presented with worsening respiratory distress over a 7-day period with clinical signs of cardiac tamponade following a history of a gunshot (with associated liver laceration, pulmonary embolism, right nephrectomy, and sepsis) 47 days prior. Transthoracic echocardiography showed a large circumferential pericardial effusion and an RVA. The patient was emergently taken for surgical repair of the RVA. Discussion: Our case presents a delayed presentation of a gunshot heart and an aetiology with indications of and against a true aneurysm. It brings attention to possible complications of penetrating precordial injuries, with the need for consideration and possible evaluation at follow-up. The literature on the operative excision of RVA is reviewed and various aetiological factors and consequences are discussed.